2021
DOI: 10.2528/pierm21032803
|View full text |Cite
|
Sign up to set email alerts
|

First Microwave Tomography Approach Towards a Truly Noninvasive, Pain-Free and Wearable Blood Glucose Monitoring Device

Abstract: Despite the advancements in the field of glucose monitoring sensors, the development of noninvasive, wearable, continuous and comfortable systems is still a real challenge. New technologies are required for noninvasive, continuous and effective measurements remaining discreet, painless, comfortable to the patient and avoiding additional costs. This article presents a truly noninvasive microwave tomography prototype designed for glucose monitoring. The system is based on an array of dipole antennas placed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Microwave testing has been applied in varied fields, like aerospace engineering [9], mechanical engineering, food engineering [10], [11], petroleum engineering, chemical engineering [12], civil engineering, forestry and medical science. Taking the last type as an example, research has been conducted on the detection of skin cancer [13], breast cancer [14], neck diseases [15], blood glucose [16] and colonoscopy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave testing has been applied in varied fields, like aerospace engineering [9], mechanical engineering, food engineering [10], [11], petroleum engineering, chemical engineering [12], civil engineering, forestry and medical science. Taking the last type as an example, research has been conducted on the detection of skin cancer [13], breast cancer [14], neck diseases [15], blood glucose [16] and colonoscopy [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that microwave detection of intracranial hemorrhage is promising due to the change in the dielectric properties [ 10 ]. Moreover, non-invasive blood glucose detection was shown to be possible due to the variation in the blood permittivity with glucose concentration [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%